(untitled) (Huellas, 2023)
Habitually, the concept “border” has been associated with the jurisdictional limits between modern nation-states, the otherwise well-known “borderlands”. However, the concept gradually diversified, moving toward more complex situations. In this sense, the “productive frontiers” appeared, highlighting the agrarian, cattle rising and extractive frontiers; referenced in this article. Otherwise, the emergence of new forms of leisure, resulted in different types of tourism, including the vineyards. Likewise, the advance of the “viniculture frontier” was fed back by the growth of tourist activity. With the objective of analyzing this process, two cases of recent vineyards expansion were selected which stimulated the increase of tourism, more precisely in San Juan and Jujuy, both argentinean provinces. Although it is an incipient phenomenon, some similar characteristics can be marked between both spaces, where the structuring hub is real estate valorization, firstly from the tourism increase and -secondly- from wine production. All this within the framework of “real estate frontier” enlargement, a process defined from the category of “land rent”, in rural-urban transition areas.